We need to find the second derivative for the equation:

`x^3 + y^3 = 1`

`==> 3x^2 + 3y^2 y' = 0`

`==> 3y^2y' = -3x^2`

``Now we will differentiate again:

==> `(3y^2)'(y')+(3y^2)(y')' = (-3x^2)'`

`==> 6yy' + 3y^2y'' = -6x`

`==> 3y^2y'' = -6x-6yy'`

`==> y'' = (-6(x+yy'))/(3y^2)`

`==> y'' = (-2(x+yy'))/y^2`

`=> y'' = (-2(x+y(-x^2/y^2)))/y^2`

`==> y'' = (-2(x -x^2/y))/y^2 = (-2(xy-x^2)/y))/y^2 = (-2(xy-x^2))/y^3`

`==> y'' = (-2x(y-x))/y^3`

``

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.